Pusa Aushadhi: a new bitter gourd variety - Behera, T K; Munshi, A D (Indian Horticulture, 2019)
Pusa Aushadhi developed though hybridization followed by single plant selection from a cross between gynoecious line DBGy201 and Pusa Do Mausami at IARI, New Delhi, has higher female:male flower ratio (7:1) compared to commercial variety, Pusa Do Mausami (1:9). Its fruits are light green, medium long and medium thick with 7-8 continuous narrow ridges. It matures in 48- 55 days, producing 12.8 tonnes/ha fruits. The nutrient content and antioxidant activities in its fruits are better than Pusa Do Mausami. It is suitable for commercial cultivation in Rajasthan, Gujarat, Haryana and Delhi. It has been recommended by Central Sub-committee on Crop Standards, Notification and Release of Varieties of Horticultural Crops for notification.